Modern Methods of Teaching Russian as a Foreign Language in a National School (Uzbekistan Open Conference, 2025)
The article discusses modern methods of teaching Russian as a foreign language aimed at developing communicative, intercultural, and media literacy competencies. The focus is on the integration of digital technologies, media education, and project-based learning into the educational process. Communicative, activity-based, and media approaches are considered key tools for fostering students’ independence, critical thinking, and speech activity.